PH dependency of the binding of (3H)BAY U 3405 and various non-labelled ligands to the thromboxane A2/prostaglandin H2 receptor of human platelet membranes - Theis, Jochen G.; Dellweg, Hansgeorg; Perzborn, Elisabeth; Groß, Rainer (European journal of pharmacology. Molecular pharmacology, 1992)
[3H]BAY U 3405 was used to characterize the effect of acidic and alkaline pH values on the binding of the thromboxane A2/prostaglandin H2 (TXA2/PGH2) receptor of human platelet membranes. The specific binding of [3H]BAY U 3405 largely increased upon acidification up to pH 5.8. Saturation binding studies revealed an increase in binding affinity without change in the number of binding sites. At pH 7.4 the Kd was 8.7 ± 3.7 nM (Bmax = 6.6 ± 0.6 pmol/mg protein) compared to 1.2 ± 0.2 nM(Bmax = 6.1 ± 0.6 pmol/mg protein) at pH 5.8. A more than 10-fold higher rate of association was observed at pH 5.8 compared to pH 7.4, while the rate of dissociation showed only minor changes. The kinetically derived dissociation constant was 1 nM (pH 5.8) and 9.6 nM (pH 7.4). The pH dependency of the binding of structurally different non-labelled ligands to the TXA2/PGH2 receptor was evaluated by inhibition studies at pH 5.8 and pH 7.4. BAY U 3405, daltroban, CTA2, and U 46619 showed significantly higher affinities at pH 5.8. In contrast, I-PTA-OH and GR 32191 had a higher affinity at pH 7.4. No significant difference was seen with SQ 29548 at the observed pH values. A second protonable group within the molecules I-PTA-OH, GR 32191, and SQ 29548 might be responsible for the observed differences.
Im Titel ist "2" jeweils tiefgestellt und "3" hochgestellt, (3H) steht dabei in eckigen Klammern
Elektronische Reproduktion der Druck-Ausgabe 21. Februar 2003
Gesehen am 08.05.2025